STRAIN RATES FOR THE SOUTHERN SIBERIAN CRATON DERIVED FROM GPS MEASUREMENTS - S. V. Ashurkov (Геодинамика и тектонофизика, 2022)
This paper presents quantitative estimates of the strain rates for the southern part of the Siberian craton derived from GPS data. The obtained results confirmed the theoretical concept of low strain rates (10–9×year–1) in the intra-platform areas. The paper is based on raw measurement data from open sources, previously reported displacement velocities, and measurement data from the Laboratory of Recent Geodynamics of the Institute of the Earth's Crust SB RAS. It is shown that of the 5 mentioned EFT-CORS stations, the BRTK site (Bratsk city) cannot be used to estimate the longterm velocity of the Siberian craton.